The impairment of HCCS leads to MLS syndrome by activating a non‐canonical cell death pathway in the brain and eyes. Issue 2 (22nd January 2013) - Indrieri, Alessia; Conte, Ivan; Chesi, Giancarlo; Romano, Alessia; Quartararo, Jade; Tatè, Rosarita; Ghezzi, Daniele; Zeviani, Massimo; Goffrini, Paola; Ferrero, Ileana; Bovolenta, Paola; Franco, Brunella
Abstract Mitochondrial‐dependent (intrinsic) programmed cell death (PCD) is an essential homoeostatic mechanism that selects bioenergetically proficient cells suitable for tissue/organ development. However, the link between mitochondrial dysfunction, intrinsic apoptosis and developmental anomalies has not been demonstrated to date. Now we provide the evidence that non‐canonical mitochondrial‐dependent apoptosis explains the phenotype of microphthalmia with linear skin lesions (MLS), an X‐linked developmental disorder caused by mutations in the holo‐cytochrome c‐type synthase (HCCS) gene. By taking advantage of a medaka model that recapitulates the MLS phenotype we demonstrate that downregulation of hccs, an essential player of the mitochondrial respiratory chain (MRC), causes increased cell death via an apoptosome‐independent caspase‐9 activation in brain and eyes. We also show that the unconventional activation of caspase‐9 occurs in the mitochondria and is triggered by MRC impairment and overproduction of reactive oxygen species (ROS). We thus propose that HCCS plays a key role in central nervous system (CNS) development by modulating a novel non‐canonical start‐up of cell death and provide the first experimental evidence for a mechanistic link between mitochondrial dysfunction, intrinsic apoptosis and developmental disorders.